Linux® Programming by Example - Robbins, Arnold (Prentice Hall Open Source Software Development Ser., 2004)
"This is an excellent introduction to Linux programming. The topics are well chosen and lucidly presented. I learned things myself, especially about internationalization, and I've been at this for quite a while." -Chet Ramey, Coauthor and Maintainer of the Bash shell "This is a good introduction to Linux programming. Arnold's technique of showing how experienced programmers use the Linux programming interfaces is a nice touch, much more useful than the canned programming examples found in most books." -Ulrich Drepper, Project Lead, GNU C library "A gentle yet thorough introduction to the art of UNIX system programming, Linux Programming by Example uses code from a wide range of familiar programs to illustrate each concept it teaches. Readers will enjoy an interesting mix of in-depth API descriptions and portability guidelines, and will come away well prepared to begin reading and writing systems applications. Heartily recommended." -Jim Meyering, Coauthor and Maintainer of the GNU Core Utility Programs Learn Linux® programming, hands-on... from real source code This book teaches Linux programming in the most effective way possible: by showing and explaining well-written programs. Drawing from both V7 Unix® and current GNU source code, Arnold Robbins focuses on the fundamental system call APIs at the core of any significant program, presenting examples from programs that Linux/Unix users already use every day. Gradually, one step at a time, Robbins teaches both high-level principles and "under the hood" techniques. Along the way, he carefully addresses real-world issues like performance, portability, and robustness. Coverage includes: Memory management File I/O File metadata Processes Users and groups Sorting and searching Argument parsing Extended interfaces Signals Internationalization Debugging And more... Just learning to program? Switching from Windows®? Already developing with Linux but interested in exploring the system call interface further? No matter which, quickly and directly, this book will help you master the fundamentals needed to build serious Linux software. Companion Web Sites, authors.phptr.com/robbins and www.linux-by-example.com , include all code examples.